Вплив регуляторів росту на регенерацію пагонів рослин Hypericum perforatum L. та Taraxacum officinalis L. - Сидорук, О.С.; Сідляк, Г.В.; Матвєєва, Н.А. (Фактори експериментальної еволюції організмів, 2015)
Aims. The aim of our work was to compare the frequency of plant regeneration of H. perforatum from the leaves,
internodes and roots and frequency of plant regeneration Т. officinalis using the proximal, middle and distal part of a leaf.
We also determined the optimal type of an explant for maximal plant regeneration frequency. Methods. For induction
of regeneration of H. perforatum and Т. officinalis shoots we used MS culture medium added with BAP, kinetin and
NAA. We used leaves, internodes and roots of the H. perforatum aseptic plants. We also used proximal, middle and
distal parts of Т. officinalis leaves. Results. MS medial supplemented by NAA and different cytokinins differed in their
ability to induce plant regeneration. The presence of these growth regulators almost in all cases stimulated the formation
of shoots for H. perforatum explants. Using of kinetin in MS medium have led to inhibition of plant regeneration from
H. perforatum leaves and resulted in low (20–60 %) regeneration frequency of Т. officinalis. Using of BAP and NAA
was the most effective for increasing of plant regeneration frequency of H. perforatum and Т. officinalis up to 100 %.
Conclusions. H. perforatum internodes and proximal parts of T. officinalis leaves possessed the greatest regenerative
ability. The proximal, medial and distal leaves parts have differed in sensitivity to growth regulators. The maximum
regeneration rate of 100 % was observed cultivating proximal leaves on three different media of 12 investigated.
Keywords: Hypericum perforatum, Taraxacum officinalis, regeneration, 6-benzylaminopuryn, kinetin.